Teori belajar kognitivisme : jean piaget theory dan implementasiannya dalam pembelajaran bahasa arab - Hotimah, Khusnul (Maliki Interdisciplinary Journal, 2025)
This article discusses the cognitivism learning theory developed by Jean Piaget, as well as its implementation in Arabic language learning. Piaget’s theory explains that children’s cognitive development consists of four main stages: schema, assimilation, accommodation, equilibration. Each stage has unique characteristics that affect how children understand and process information. In the context of Arabic language learning, understanding these stages is important so that teaching can be tailored to students’ cognitive development. The implementation of Piaget’s theory in Arabic language learning includes the use of methods that support exploration, active interaction and independent knowledge construction by students. By customizing Arabic teaching strategies based on the stages of cognitive development, teachers can increase the effectiveness of the learning process and facilitate a deeper understanding of the language. The article also highlights the importance of the teacher’s role in designing appropriate materials and activities, as well as the challenges that may be faced in implementing Piaget’s theory of cognitivism in the Arabic language classroom.